Fluoride-resistant Streptococcus mutans within cross-kingdom biofilms support Candida albicans growth under fluoride and attenuate the in vitro anti-caries effect of fluorine - Sun, Yan; Chen, Yanhan; Du, Qian; Zhang, Jin; Xu, Muxin; Zheng, Gaozhe; Zhou, Wen; Zhou, Xinxuan; Qiu, Lili; Pan, Yihuai; Zhang, Keke (Frontiers in Microbiology, 2024)
Fluoride-resistant Streptococcus mutans (S. mutans) might affect the ecological balance of biofilms in the presence of fluoride. We used a S. mutans and Candida albicans (C. albicans) cross-kingdom biofilm model to investigate whether fluoride-resistant S. mutans within biofilm would support C. albicans under fluoride stress and attenuate the in vitro anti-caries effect of fluorine. The impact of fluoride-resistant S. mutans on cross-kingdom biofilm formation by S. mutans and C. albicans in the presence of fluoride was investigated in vitro using the crystal violet assay. Biofilm constitution was determined using colony-forming unit (CFU) counts and fluorescent in situ hybridization (FISH). Extracellular polysaccharides (EPS) generation in biofilms was determined by EPS/bacterial dyeing and water-insoluble polysaccharide detection. Acid production and demineralization were monitored using pH, lactic acid content, and transversal microradiography (TMR). The gene expression of microorganisms in the cross-kingdom biofilm was measured using qRT-PCR. Our results showed that both C. albicans and fluoride-resistant S. mutans grew vigorously, forming robust cross-kingdom biofilms, even in the presence of sodium fluoride (NaF). Moreover, fluoride-resistant S. mutanscontaining cross-kingdom biofilms had considerable cariogenic potential for EPS synthesis, acid production, and demineralization ability in the presence of NaF than fluoride-sensitive S. mutanscontaining biofilms. Furthermore, the gene expression of microorganisms in the two cross-kingdom biofilms changed dissimilarly in the presence of NaF. In summary, fluoride-resistant S. mutans within cross-kingdom biofilms supported C. albicans growth under fluoride and might attenuate the anti-caries potential of fluorine by maintaining robust cross-kingdom biofilm formation and cariogenic virulence expression in vitro in the presence of NaF.